"Keep It Going, Girl!" An Empirical Analysis of Gender Differences and Inequalities in Computer Sciences. (2018) - Förtsch, Silvia; Gärtig-Daugs, Anja; Buchholz, Sandra; Schmid, Ute
No abstract available